Kemampuan Pemecahan Masalah dan Kreativitas Peserta Didik dengan Pendekatan Berpikir Kausalitik Berscaffolding - Faisal Faisal; Joni Rokhmat; Jannatin Ardhuha (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This research aimed to investigate problem-solving ability (PSA) and creativity of students through physics learning with causalitic-thinking approach with scaffolding of type 2b. With the scaffolding, in learning, students have to determine all causes and predict all possible effects in a phenomenon, also give arguments how conditions of each cause so that each effect occur. However, the number of the causes and effects is informed and part of the causes, effects, and arguments also be given so the students only need to complete them. This research used method of experiment with control group design. As population were students of class XI MIA SMAN 3 Mataram year 2017/2018 while as sample were the students of class XI MIA 8 and XI MIA 9. Data of the PSA and creativity were taken by using one set of test instrument and respectively analyzed with t-test and U-test at significance level of 5%. The former test showed that tcounted is 12.621 with ttable of 2.004 which meant that the approach affected PSA of students. While, the latter one showed that zcounted is 6.69 with ztable of 1.96 which meant that the approach also affected creativity of students.